2020
DOI: 10.1002/eap.2112
|View full text |Cite
|
Sign up to set email alerts
|

A need for speed in Bayesian population models: a practical guide to marginalizing and recovering discrete latent states

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 50 publications
(35 reference statements)
5
52
0
Order By: Relevance
“…Test sequence: 000000− / N animals: 0 Test sequence: 000000− / N animals: 197 The forward algorithm is a type of marginalisation that partly explains the better performance of the Stan version of the model. However, (Yackulic et al, 2020) also compared the speed of the marginalised versions of their model in different programmes and observed that Stan was orders of magnitude faster than JAGS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Test sequence: 000000− / N animals: 0 Test sequence: 000000− / N animals: 197 The forward algorithm is a type of marginalisation that partly explains the better performance of the Stan version of the model. However, (Yackulic et al, 2020) also compared the speed of the marginalised versions of their model in different programmes and observed that Stan was orders of magnitude faster than JAGS.…”
Section: Discussionmentioning
confidence: 99%
“…showed that the marginalisation of the latent states considerably reduces the time needed to estimate the parameters of such models while returning the same estimates. We did not implement this approach in JAGS, although this would have been possible using the ones trick, as explained in the article by Yackulic et al (2020). The forward algorithm is a type of marginalisation that partly explains the better performance of the Stan version of the model.…”
Section: Predicted Probabilities Of Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…2005, Kéry and Royle 2015, Yackulic et al. 2020). For each b = 1, … B removal period, our marginal likelihood is defined asyr,i,j,t,bPoisson0.166667emλr,i,j,t·πr,i,j,t,bwhere π r , i , j , t is equivalent to πr,i,j,t* but does not include the probability of failing to detect an individual that was truly present.…”
Section: Methodsmentioning
confidence: 99%